2017
DOI: 10.1371/journal.pone.0184090
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly of a transcriptome from the eggs and early embryos of Astropecten aranciacus

Abstract: Starfish have been instrumental in many fields of biological and ecological research. Oocytes of Astropecten aranciacus, a common species native to the Mediterranean Sea and the East Atlantic, have long been used as an experimental model to study meiotic maturation, fertilization, intracellular Ca2+ signaling, and cell cycle controls. However, investigation of the underlying molecular mechanisms has often been hampered by the overall lack of DNA or protein sequences for the species. In this study, we have asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 118 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…Relative expression profiles of DEGs in the both resistant and susceptible evaluated using qRT-PCR were in complete agreement with the RNA-Seq data. This is in line with other studies, which showed almost the same level of fold changes between RNA-Seq data and qPCR [67,68].…”
Section: Validation Of Degs By Using Qrt-pcrsupporting
confidence: 93%
“…Relative expression profiles of DEGs in the both resistant and susceptible evaluated using qRT-PCR were in complete agreement with the RNA-Seq data. This is in line with other studies, which showed almost the same level of fold changes between RNA-Seq data and qPCR [67,68].…”
Section: Validation Of Degs By Using Qrt-pcrsupporting
confidence: 93%
“…In mammalian eggs, for example, a sperm-specific isoform PLCζ is accountable for generating Ca 2+ waves at fertilization [31,32]. PLCζ, however, does not seem to exist in the genome or transcriptome of sea urchin and starfish [33][34][35], and the InsP 3 -dependent Ca 2+ increase in the fertilized eggs of echinoderms is mostly attributable to PLCÉŁ [36][37][38], which is shown to be activated by Src-family kinase that interacts with the SH domain of PLCÉŁ within 15 sec after fertilization [39][40][41]. Even so, questions still remain on how Src-family kinases are activated by their upstream signaling molecules on the egg surface.…”
Section: Introductionmentioning
confidence: 99%
“…Mah and Foltz (2011) have reported in living taxa among the Neoasteroidea that the Asteroidea is divided into two superorders; one for Valvatacea including the orders Valvatida and Paxillosida, and another for Forcipulatacea including the order Forciplatida. Recently, a phylogenetic analysis using cytochrome c oxidase subunit 1 gene revealed that Paxillosida and Valvatida species are involved in the same cluster, but Forcipulatida species are in a different cluster (Musacchia et al, 2017). Altogether, the molecular phylogenetic position of AscRGP and PpeRGP is in good agreement with the latest starfish taxonomy.…”
Section: Discussionmentioning
confidence: 99%